Alcohol consumption and mortality: the Ludwigshafen Risk and Cardiovascular Health (LURIC) study - Moissl-Blanke, Angela P.; Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; Dawczynski, Christine; Stojakovic, Tatjana; März, Winfried; Kleber, Marcus E.; Lorkowski, Stefan (Atherosclerosis, 2021)
Background and aims - One of the most important risk factors for morbidity and mortality is the consumption of alcohol. The aim of our study was to examine the effect of alcohol consumption on all-cause mortality and cardiovascular mortality. - Methods - The Ludwigshafen Risk and Cardiovascular Health (LURIC) study includes 3316 patients hospitalized for coronary angiography at a tertiary care centre in Southwest Germany. Patients were followed-up for a median of 9.9 (range 0.1-11.9 years) years. Total mortality number in the follow-up period was 995, and the number of incident cases, i.e. cardiovascular death, was 622. Information on alcohol consumption assessed by self-report questionnaires was used to calculate intake in grams of ethanol per day. Associations of alcohol consumption with morbidity and mortality were analysed using Cox proportional hazards regression. - Results - We found significantly increased mortality for patients in the highest alcohol intake group age- and sex-adjusted (hazard ratio of 1.59 (95%CI, 0.93-2.72)) and a reduced risk for the group of low-volume drinkers (hazard ratio of 0.75 (95%CI, 0.65-0.86)). After adjustment for cardiovascular risk factors, the risk difference between abstainers and low-volume drinkers was not significant anymore. - Conclusions - In the LURIC study, the risk of overall mortality and cardiovascular mortality is significantly increased in study participants with very high alcohol consumption and slightly increased in total abstainers as compared to participants with low consumption in unadjusted analysis, replicating the well-known J-curve. Adjusting for cardiovascular risk factors rendered the risk decrease observed for low-volume drinkers insignificant. Therefore, our results do not show a significant health benefit of low-volume alcohol consumption in a cohort of patients at medium-to-high cardiovascular risk.
Online verfügbar: 12. August 2021, Artikelversion: 8. Oktober 2021
Gesehen am 12.11.2025